The Synthetic Map of Territorial Development: web geographical tool for the support in the territorial decision making - Martínez Cebolla, Rafael; López Martín, Fernando; Portolés Rodríguez, David (Geographicalia, 2014)
CINTA works on the principle of offering assistance to the Spatial Planning Agency of the Government of Aragon in supporting territorial decision making. Its cognitive effort, thanks to advances in Geographic Information Technologies, has focused on developing a web application that reflects synthetically a territorial diagnosis of Aragón. This paper deals with Synthetic Map of Territorial Development as a useful aid to reflect the status of aragonese territory in a visual way, and how possible interventions on territory could affect, in a positive or negative way, depending on relational elements involved on spatial planning.
Keywords: synthetic indicator; territorial model; management of the territory; territorial planning; territorial development; gis information system